The moderating effect of human capital on the relationship between social capital and business performance among agripreneur: A study in Kota Tinggi, Johor - Lee, Esther Fang Yong (2016)
This study aims to examine the influence of social capital on business performance among agripreneur in Kota Tinggi, Johar. The moderating effect of human capital (training) on the relationship between social capital and business performance among agripreneur is also assessed. The study employed a survey questionnaire with a purposive sampling method to collect data from 161 vegeta ble agripreneur in Kota Tinggi. SPSS Version 22 and Smart PLS 2.0 were used to analyze the data. The result of the study indicated that the dimensions of social capital which are structural and cognitive has a significant positive effect on business performance among agripreneur. Whereby, there is a direct relationship between human capital (training) on business performance among agripreneur. However, there is no moderating effect of human capital (training) on the relationship between social capital and business performance. The study gives an insight to policy maker to create awareness about· the existence and benefits of agripreneur regarding to provide training programme on their agribusiness in the local areas. For researcher, other fa:tors needed to be further in future research. For the prospect of agripreneur, training is needed before they begin their venture in agribusiness. Lastly, training is important to existing agripreneur to enrich their business performance.